Exploring Pre-service Teachers’ Voices Through Photovoice: Basis for Recreating Academic Green Spaces - Pineda, Anne Lorraine; Marasigan, Arlyne (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences and critical perspectives of pre-service teachers regarding academic green spaces through a qualitative participatory research design using the Photovoice approach. Anchored on the participatory principles of Wang & Burris (1997) and the thematic analysis framework of Braun and Clarke (2006), the study examined how academic green spaces contribute to students’ well-being, learning experiences, and environmental awareness. The research was conducted at a Philippine Higher Education Institution with a Center of Excellence in Teacher Education during the Academic Year 2024–2025 and involved twenty-two (22) science pre-service teachers selected through purposive sampling. Data were gathered through Photovoice SHOWED guide questions, participants’ photographs, reflective narratives, and focus group discussions. The collected data were analyzed using thematic analysis to identify recurring patterns and themes related to the significance, challenges, and improvement of academic green spaces. Findings revealed that the majority of participants perceived academic green spaces as highly important in promoting stress reduction, emotional well-being, social interaction, reflective learning, and environmental awareness. Participants identified several benefits of green spaces, including relaxation, improved concentration, better social interaction, and increased motivation to study. However, challenges such as inadequate maintenance, insufficient shaded and seating areas, poor waste management, and limited student participation in environmental planning were also observed. The study further emphasized the importance of student participation in campus environmental planning and sustainability initiatives. The study concluded that academic green spaces play a significant role in creating inclusive, learner-centered, and sustainable educational environments. It recommended strengthening campus greening programs, improving maintenance and access, implementing effective waste management practices, and increasing student involvement in environmental decision-making processes. The study supports Sustainable Development Goal (SDG) 3 on Good Health and Well-Being, SDG 4 on Quality Education, SDG 11 on Sustainable Cities and Communities, and SDG 13 on Climate Action by emphasizing the importance of sustainable and inclusive green learning environments. Its sustainability impact lies in promoting environmental stewardship, participatory campus planning, student well-being, and sustainable institutional practices within higher education.
Keywords: Academic Green Spaces; Environmental Awareness; Participatory Research; Photovoice; Pre-Service Teachers; Reflective Learning; Student Well-Being; Sustainability; Thematic Analysis; Waste Management